(untitled) (Journal of Information Technology and Digital World, 2020)
Auto mode vehicles are also called as auto pilot vehicles which are running with the help of programmed artificial intelligence. As of now the auto pilot vehicles are designed to operate for certain distance by analyzing the alertness of driver through his physical presence. The physical presence is verified by reading the driver’s touch signal to the steering connected in a vehicle. The proposed system is designed to enhance the safety feature of a vehicle by analyzing the driver’s alertness through his mind wave. The mind wave signal variations are continuously monitored through a microcontroller and it will enables the auto pilot mode when there is an emergency. The auto pilot mode enabled at such situations are designed to avoid accidents by stopping the vehicle in a safety manner. The prototype of the design is verified in the paper by conducing several experiments.